The Use Of Animational Fairytyle Video Media To Improve Narrative Writing Skills In Class IV SD Students During The Covid 19 Pandemic - Bekti Lestari; Enny Zubaidah (Indonesian Journal of Basic Education, 2021)
This study aims to improve the skills of writing narrative essays using animated video media containing fairy tales for the fourth grade students of SD N Tunjungsari 2, Kalasan, Sleman. This research is a classroom action research (CAR) using the Stephen Kemmis & Mc. Taggart which is done through 2 cycles. The subjects in this study were the fourth grade students of SD N Tunjungsari 2 as many as 30 students. The collection techniques used in this study were observation, practical tests, and written tests. The data analysis technique in this study was qualitatively analyzed using the interactive abaysis technique from Miles & Hubberman. The results of this study indicate that students' skills in writing narrative essays increased after the action using animated video media from cycle 1 to cycle 2. Narrative writing skills in cycle 1 achieved an average score of 79.01, and in cycle 2 achieved an average score. -average 82.22, where as many as 27 students (90%) got a score with a minimum criteria of good. The results of the scores achieved in cycle 2 showed an increase in narrative essay writing skills in fourth grade students of SD N Tunjungsari 2.